2011
DOI: 10.1073/pnas.1108320108
|View full text |Cite
|
Sign up to set email alerts
|

NMR basis for interprotein electron transfer gating between cytochrome c and cytochrome c oxidase

Abstract: The final interprotein electron transfer (ET) in the mammalian respiratory chain, from cytochrome c (Cyt c ) to cytochrome c oxidase (C c O) is investigated by 1 H- 15 N heteronuclear single quantum coherence spectral analysis. The chemical shift perturbation in isotope-labeled Cyt c induced by addition of unlabeled C c O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
71
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 34 publications
(42 reference statements)
11
71
0
Order By: Relevance
“…Interestingly, Cc uses the same surface surrounding the heme crevice (Fig. 4) to interact with all novel interaction partners as earlier studies have shown it to do with its physiological redox partners, namely, cytochrome c 1 (53), cytochrome-c peroxidase (54), and cytochrome-c oxidase (55) . Fig.…”
Section: Exploring Novel CC Protein Interaction Partners Using Amentioning
confidence: 93%
“…Interestingly, Cc uses the same surface surrounding the heme crevice (Fig. 4) to interact with all novel interaction partners as earlier studies have shown it to do with its physiological redox partners, namely, cytochrome c 1 (53), cytochrome-c peroxidase (54), and cytochrome-c oxidase (55) . Fig.…”
Section: Exploring Novel CC Protein Interaction Partners Using Amentioning
confidence: 93%
“…These residues are surrounding the heme crevice and constitute the interaction surface (Fig. 2c), which is very well-conserved among complexes involving c-type cytochromes [14,29,[46][47][48][49][50][51][52][53][54][55]. In addition, significant CSP are detected (Dd avg -P 0.05 ppm) for Lys7, Lys13, Val20, Ser47, Lys73, Val83, Lys88 and Ala92.…”
Section: The Heterologous Hcc-pcc 1 Complexmentioning
confidence: 99%
“…Recently, the surface residues of hCc contacting bovine CcO have been mapped by NMR [52]. However, no evidences on the stoichiometry and binding affinity of the Cc-CcO complex were elucidated by NMR.…”
Section: Interaction Between Hcc and Bovine Ccomentioning
confidence: 99%
“…Recently, however, we successfully identified the interaction site for CcO on Cyt c using NMR spectroscopy (13). Our NMR analysis using chemical shift perturbations clearly indicated positively charged residues, including several Lys residues (Lys-5, Lys-7, Lys-8, Lys-13, Lys-79, Lys-86, Lys-87, and Lys-88), located in the interaction site for CcO on Cyt c, as we expected (10,14).…”
mentioning
confidence: 99%
“…Our NMR analysis using chemical shift perturbations clearly indicated positively charged residues, including several Lys residues (Lys-5, Lys-7, Lys-8, Lys-13, Lys-79, Lys-86, Lys-87, and Lys-88), located in the interaction site for CcO on Cyt c, as we expected (10,14). In addition to the positively charged residues, several negatively charged residues such as Glu-4, Glu-89, Glu-90, and Asp-93 and some hydrophobic residues such as Ile-9, Ile-11, Met-12, and Ile-81 are also present in the interaction site for CcO, indicating that both electrostatic and hydrophobic interactions would contribute to ET complex formation between CcO and Cyt c, regulating the ET reaction from Cyt c to reduce molecular oxygen and promote proton pumping in CcO (13).…”
mentioning
confidence: 99%